(untitled) (West Hartford, Conn., 1994)
The handbook consists of thirty-nine original cases by contributors from the global North and South including Latin America, Asia, and Africa. From agricultural production to post-harvest activities, this handbook offers a practical set of tools for anyone interested in gender analysis in agriculture
Keywords: Women in agriculture,Phụ nữ trong nông nghiệp; Case studies,Nghiên cứu tình huống; Developing countries,Các nước đang phát triển